2010
DOI: 10.1103/physrevd.82.035019
|View full text |Cite
|
Sign up to set email alerts
|

Complex scalar dark mattervis-à-visCoGeNT, DAMA/LIBRA, and XENON100

Abstract: The CoGeNT and DAMA/LIBRA experiments have found evidence for the spin-independent scattering from nuclei of a light dark matter (DM) particle, 7-12 GeV, which is not excluded by the XENON DM experiments. We show that this putative DM signal can be explained by a complex scalar singlet extension of the standard model (CSM), with a thermal cosmological DM density, and a Higgs sector that is consistent with LEP constraints. We make predictions for the masses, production, and decays of the two Higgs mass eigensta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 105 publications
(126 reference statements)
1
60
0
Order By: Relevance
“…Except for a typical assumption of S-wave annihilation our results are largely model-independent, so all the particle-physics scenarios motivated by DAMA/LIBRA and CoGeNT results Andreas et al 2010;Chang et al 2010;Foot 2010;Barger et al 2010b;Hooper et al 2010;Essig et al 2010;Barger et al 2010a;Cline et al 2011;Buckley et al 2011) including theoretically wellmotivated particle physics models that predict light DM, such as the MSSM (Feldman et al 2010;Kuflik et al 2010;Fornengo et al 2011;Bottino et al 2010) and the NMSSM (Kang et al 2011;Belikov et al 2011;Gunion et al 2010;Draper et al 2011), are stringently tested by WMAP and Planck.…”
Section: Cmb Constraintsmentioning
confidence: 99%
“…Except for a typical assumption of S-wave annihilation our results are largely model-independent, so all the particle-physics scenarios motivated by DAMA/LIBRA and CoGeNT results Andreas et al 2010;Chang et al 2010;Foot 2010;Barger et al 2010b;Hooper et al 2010;Essig et al 2010;Barger et al 2010a;Cline et al 2011;Buckley et al 2011) including theoretically wellmotivated particle physics models that predict light DM, such as the MSSM (Feldman et al 2010;Kuflik et al 2010;Fornengo et al 2011;Bottino et al 2010) and the NMSSM (Kang et al 2011;Belikov et al 2011;Gunion et al 2010;Draper et al 2011), are stringently tested by WMAP and Planck.…”
Section: Cmb Constraintsmentioning
confidence: 99%
“…Once the constraint from DM relic abundance is imposed, the number of independent model parameters is reduced to one. Since previous experimental data has excluded a fermionic DM (except for the pseudo-scalar coupling) [3], we focus on either a real or complex scalar DM, on which early studies can be found in [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and [21][22][23][24][25][26][27] , respectively. 1 In the light of the direct detection arising from the LUX 2016 data, the indirect detection arising from the Higgs invisible decay at LHC [29], and the indirect detection arising from gamma ray spectrum induced by DM annihilation at Fermi-LAT [30,31] and HESS [32], the DM mass regions are updated as follows.…”
Section: Introductionmentioning
confidence: 99%
“…: SUSY particles (as neutralino [21] or sneutrino in various scenarios [22]), inelastic Dark Matter in various scenarios [23,24], electron interacting dark matter (including WIMP scenarios) [10], a heavy neutrino of the 4-th family, sterile neutrino [11], Kaluza-Klein particles, self-interacting dark matter, axion-like (light pseudoscalar and scalar candidate) [6], mirror dark matter in various scenarios [25], Resonant Dark Matter [26], DM from exotic 4th generation quarks [27], Elementary Black holes, Planckian objects, Daemons, Composite DM [28], Light scalar WIMP through Higgs portal [29], Complex Scalar Dark Matter [30], specific two Higgs doublet models, exothermic DM [31], Secluded WIMPs [32], Asymmetric DM [33], Isospin-Violating Dark Matter [34], Singlet DM [35], Specific GU [36], SuperWIMPs [37], WIMPzilla [38], etc. [39].…”
Section: Introductionmentioning
confidence: 99%